ANALISIS PENGARUH KUALITAS PRODUK TELUR AYAM TERHADAP HARGA ECERAN TERTINGGI TELUR AYAM PADA PENGUSAHA AYAM PETELUR TULUNGAGUNG - Siswo Adie (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2017)
This study aims to analyze product quality factors consisting of durability, suitability of specifications, and aesthetics affecting the highest retail price of chicken egg product Tulungagung chicken hen, both simultaneously and partially, and to determine which variables have a dominant influence. The type of research used by this researcher is an explanatory research, which explains the causal relationship between variables through hypothesis testing. The sample of this research is 60 respondents from hens entrepreneurs in Tulungagung. In determining the sample of researchers using pruposive sampling method. Data analysis technique used is using multiple linear regression calculated with the help of software program SPSS version 17.0 for windows.The result of this research by using multiple regression analysis indicate that simultaneously variable of endurance, conformity with specification, and aesthetics influencing the highest retail price of egg product of Tulungagung chicken hens with significance level of 0.000 and coefficient of determination 0,837 or (83,7%) . While the partial variable endurance, suitability specifications, and aesthetics affecting the highest retail price of egg products Tulungagung chicken hens with the level of significance of each variable of variable 0.000 durability, compliance with 0.000 specifications and est. 0.018. The variable that dominantly influence to the highest retail price of egg product of Tulungagung chicken hens is variable of endurance.From this research, it is expected that the company can better understand again the quality of the product consisting of variable durability, suitability of specifications, and aesthetics affecting the highest retail price of egg products Tulungagung chicken hens, so that the retail price of chicken egg product of chicken farmers Nganjuk can Improved again.